A Meta‐Analysis on the Return on Investment of Geospatial Data and Systems: A Multi‐Country Perspective. Issue 2 (11th August 2014) - Trapp, Natalie; Schneider, Uwe A.; McCallum, Ian; Fritz, Steffen; Schill, Christian; Borzacchiello, Maria Teresa; Heumesser, Christine; Craglia, Max
Abstract The availability, quality and accessibility of Geographic Information (GI) have significant socio‐economic and environmental benefits, but the collection and maintenance of GI require substantial investments. Cost‐benefit assessments (CBAs) attempt to justify the costs of geospatial data investments, applying different methodologies and focusing on diverse areas. Therefore, the Returns on Investment (ROI) vary considerably across studies, regions and sectors. The objective of this study is to explain some of the variation in the average ROI of GI by conducting a meta‐analysis of 82 cost‐benefit assessments between 1994 and 2013. In a first step, CBAs are systematically reviewed and relevant information is extracted. Particular emphasis is given to investment conditions and study characteristics. In a second step, multivariate regression methods are used to assess the size, significance and direction of individual effects. The results suggest that regional factors have the largest impact on the profitability of GI. Returns in Australia and New Zealand, for example, are four times larger than in Europe. In addition, small‐scale regional investments have a 2.5 times lower return than large‐scale international investments. Overall, the expected benefits of GI investments are approximately 3.2 times larger than the costs.